Portuguese manufacturing industry: determinants of new firm entry - Andraz, Georgette (2015)
The main purpose of this study is to investigate the determinants of new firm entry in the Portuguese manufacturing industries over the period 1996-2007. Estimation results generally confirm previous studies findings (see, e.g. Fotopoulos & Spence, 1998; Nystrom, 2007). Our findings indicate that market size and past macroeconomic conditions are important determinants of entry rates. Results also indicate a significant positive effect of past exit on actual entry. It is also found evidence of low barriers to new entry which associated with high firm turnover suggests companies’ inability to compete in the market, mainly due to difficulties in raising capital for required investments to operate efficiently. Results also reveal evidence of an inversed “U” shaped relationship between industry profit and entry. This result brings new line of investigation in the empirical literature on industry dynamics